2009
DOI: 10.2320/matertrans.m2009135
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Thermally Induced Nano-Quasicrystallization and Deformation-Assisted Nanocrystallization for Mechanical Property Improvement in Zr-Al-Ni-Cu-Pd Bulk Metallic Glasses

Abstract: The material design tailoring of a synergistic effect of an in-situ nano secondary phase formation and deformation-induced nanocrystallization for improving the mechanical strength and ductility, has been investigated in Zr 65 Al 7:5 Ni 10 Cu 17:5Àx Pd x bulk metallic glasses (BMGs). As-cast Zr 65 Al 7:5 Ni 10 Cu 17:5Àx Pd x (x ¼ 5{17:5) BMGs have significant ductility in compressive deformation, which is attributed to deformation-induced dynamic nanocrystallization. The 10 at% Pd-containing BMG with a low vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Repeating the process of such deformation-induced nanocrystallization, a significant plasticity is exhibited by shear band branching compared to that in deformation without any structural change. We have already reported that similar nanocrystallization induced by deformation is also observed in the BMGs with the Pd concentration over 10 at.% [10,19]. Table 1 summarizes mechanical properties of several Pdcontaining BMGs cast in ambient Ar pressure.…”
Section: Plasticity By Deformation-induced Nanocrystallization In Pd-supporting
confidence: 61%
See 1 more Smart Citation
“…Repeating the process of such deformation-induced nanocrystallization, a significant plasticity is exhibited by shear band branching compared to that in deformation without any structural change. We have already reported that similar nanocrystallization induced by deformation is also observed in the BMGs with the Pd concentration over 10 at.% [10,19]. Table 1 summarizes mechanical properties of several Pdcontaining BMGs cast in ambient Ar pressure.…”
Section: Plasticity By Deformation-induced Nanocrystallization In Pd-supporting
confidence: 61%
“…We have already clarified that plasticity is significantly improved in the Zr 65 Al 7.5 Ni 10 Cu 12.5 Pd 5 BMG cast in ambient Ar or He (∼6%), comparing to that cast in vacuum (∼2%) [18]. Here, the multiple shear bands are observed in the BMGs cast in Ar and He [19]. The measured enthalpy of relaxation is 4.4 J/g (vacuum), 8.2 J/g (ambient Ar) and 9.8 J/g (ambient He), indicating a correlation with plastic strain.…”
Section: Mechanical Properties Of Unrelaxed Bmgsmentioning
confidence: 63%
“…We have previously reported that plasticity is not lost so significantly even by the QC precipitation below its volume fraction of approximately 6% in the Zr 65 Al 7:5 Ni 10 Cu 7:5 Pd 10 BMG. 27) However, in the present alloy, it is noted that the plasticity vanishes suddenly even in the structural relaxation prior to the QC precipitation. Although the reason for it is not cleared completely, we should consider the higher nucleation rate at elevated temperature as well as a disappearance of free volume.…”
Section: )mentioning
confidence: 49%
“…The excellent plasticity in the Pd-containing BMG is caused by the synergy effect of the deformation-induced nanocrystallization and less relaxed glassy structure. [23,24] The minor additive, i.e., Pd, with a different size from others also may contribute to it by inducing the excess free volume in the glassy state. [25] Even in such case, the improvement of plastic strain with the increase of DH relax clearly indicates that the relaxation state of glassy structure is a fundamentally effective factor for deformability.…”
Section: Mechanical Properties Of Bmgs With Various Less Relaxed Gmentioning
confidence: 99%